2008
DOI: 10.1037/0894-4105.22.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in older adults: A structural equation modeling approach.

Abstract: Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to study the organization of executive functions in older adults. The four primary goals were to examine (a) whether executive functions were supported by one versus multiple underlying factors, (b) which underlying skill(s) predicted performance on complex executive function tasks, (c) whether performance on analogous verbal and nonverbal tasks was supported by separable underlying skills, and (d) how patterns of performance g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
123
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 62 publications
14
123
0
8
Order By: Relevance
“…The findings are in line with Kodl and Seaquist (2008), Qui et al (2006), Okereke et al (2008), Hull et al (2008) and Jurado and Rosselli (2007). Awad et al (2010), in a review study, showed that type 2 diabetes is more strongly correlated with memory deficiencies and executive functions.…”
Section: Discussionsupporting
confidence: 78%
“…The findings are in line with Kodl and Seaquist (2008), Qui et al (2006), Okereke et al (2008), Hull et al (2008) and Jurado and Rosselli (2007). Awad et al (2010), in a review study, showed that type 2 diabetes is more strongly correlated with memory deficiencies and executive functions.…”
Section: Discussionsupporting
confidence: 78%
“…The local/ global task is a very common measure of shifting (e.g., Hull, Martin, Beier, Lane, & Hamilton, 2008;Miyake et al, 2000;Vaughan & Giovanello, 2010) that required the child to shift between identifying shapes at the local and the global level. Both accuracy and RTs were collected.…”
Section: Task Shiftingmentioning
confidence: 99%
“…Portanto, o modelo empírico indicou a adequação de praxias construtiva e ideomotora, mas a confirmação da adequação em termos estatísticos de tarefas de praxias do tipo reflexiva requer a inclusão de um maior número de tarefas ou outro método de análise. Considerando a teoria de avaliação de funções executivas que integra a avaliação de memória de trabalho, atenção sustentada, resolução de problemas e inibição, entre outras habilidades, como planejamento, formação conceitual, desenvolvimento estratégico e implementação (Ardila, 2008;Chan, Shum, Toulopoulou, & Chen, 2008;Hull, Martin, Beier, Lane, & Hamilton, 2008;Salthouse, 2005) Ressalta-se que os componentes de atenção e memória frequentemente estão relacionados um ao outro e a outras habilidades cognitivas, por exemplo, às funções executivas, relações que ainda não foram completamente compreendidas (Ostrosky-Solís et al, 2007). Por exemplo, no que se refere à estrutura estatística do componente executivo central da memória de trabalho, Miyake et al (2000) avaliou as funções flexibilidade mental, atualização da informação e inibição da resposta predominante e concluiu que ao mesmo tempo que essas funções podem ser evidentemente distinguidas, elas também dividem algumas características.…”
Section: Instrumentosunclassified